Low-nitrogen ultra-high-purity silicon carbide raw material and synthesis method

Through high-temperature graphitization pretreatment and low-pressure turbulent gas flow design, combined with a three-stage temperature-controlled heating system and online monitoring, the nitrogen content in the silicon carbide raw material was successfully reduced, the problems of removing nitrogen impurities inside the raw material and process stability were solved, and the preparation of ultra-high-purity silicon carbide was achieved.

CN120698463APending Publication Date: 2025-09-26ANHUI WEIXIN CHANGJIANG SEMICON MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510879244.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-27
Publication Date
2025-09-26

AI Technical Summary

Technical Problem

The existing technology has difficulty in effectively removing nitrogen impurities inside the raw materials during the synthesis of low-nitrogen silicon carbide raw materials, the process stability is insufficient, and it is difficult to achieve ultra-low nitrogen content.

Method used

The carbon powder is pretreated by high-temperature graphitization, combined with a low-pressure, high-flow gas flow design. Through a multi-stage filtration device and a flow regulating valve, a three-stage independent temperature control and heating system and an online monitoring system are used to optimize the temperature gradient and pressure conditions to carry out the phase transition from α-SiC to β-SiC and the directional growth of particles.

Benefits of technology

The nitrogen content in silicon carbide raw materials is significantly reduced to below 1×1016 atoms/cm3, and the bulk density is increased to above 1.5g/cm3, ensuring the uniformity and stability of the product to meet the needs of high-end applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120698463A_ABST
    Figure CN120698463A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of silicon carbide preparation, in particular to a low-nitrogen ultra-high-purity silicon carbide raw material and a synthesis method thereof, and the synthesis method comprises the steps of raw material pretreatment, degassing and interface optimization, low-temperature phase generation, high-temperature phase conversion, sublimation-desublimation growth and the like. The initial nitrogen content of the carbon powder is reduced through high-temperature graphitization, nitrogen impurity diffusion is reduced in combination with a low-pressure large-flow gas flow design, and finally the nitrogen content is lower than 1 * 10 < 16 > atoms / cm < 3 >. A three-section independent temperature control system is adopted to accurately control a temperature field, and particle morphology and bulk density are optimized to 1.5 g / cm < 3 > or above. According to the method, the process stability can be remarkably improved, and the strict requirements of high-end application on ultra-low nitrogen content and high-purity silicon carbide raw materials are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of inorganic non-metallic materials, and specifically relates to a low-nitrogen ultra-high-purity silicon carbide raw material and a synthesis method. Background Art

[0002] Silicon carbide (SiC) is the core representative of the third generation of wide bandgap semiconductor materials. Due to its excellent performance such as wide bandgap, high thermal conductivity, and high breakdown field strength, it has become an important basic material for power electronic devices.

[0003] For example, a Chinese patent discloses: "A method for preparing silicon carbide powder with low nitrogen content and silicon carbide single crystal", publication number: CN113371712B. By adding volatile high-purity organic matter to high-purity silicon powder and high-purity graphite powder, the organic matter is volatilized under an inert atmosphere to take away nitrogen on the surface and grain boundaries of the raw materials, thereby reducing the nitrogen content of the silicon carbide powder to less than 5×10 16 / cm 3 This method is effective in removing nitrogen impurities on the surface, but has limited ability to remove nitrogen impurities buried within the raw materials (such as CN bonds in carbon powder or Si-N bonds in silicon powder). It also requires high pretreatment of the raw materials, which may lead to residual nitrogen contamination in the final product.

[0004] Another example is a Chinese patent disclosure: "A method for reducing the nitrogen impurity content in silicon carbide powder", publication number: CN110203933B. By introducing a denitrifying substance that reacts chemically with nitrogen at high temperature, the nitrogen impurities are fixed in the form of stable nitrides to prevent them from entering the silicon carbide lattice, achieving a nitrogen content of less than 2×10 16 / cm 3 However, the selection and use conditions of nitrogen removal substances in this technical solution are relatively strict, and the chemical reaction efficiency is greatly affected by temperature and atmosphere control, which may cause fluctuations in nitrogen removal effect. In addition, this method mainly removes surface nitrogen impurities and has limited ability to remove nitrogen impurities deeply buried in the raw materials.

[0005] The above issues indicate that existing low-nitrogen silicon carbide raw material synthesis technologies still have room for improvement in terms of deep removal of nitrogen impurities within the raw material, process stability, and achieving ultra-low nitrogen content. Therefore, the present invention proposes a low-nitrogen, ultra-high-purity silicon carbide raw material and synthesis method. This aims to further reduce the nitrogen content and improve the raw material purity through innovative raw material purification processes and coordinated control technologies, thereby meeting the demand for ultra-high-purity silicon carbide materials in high-end applications. Summary of the Invention

[0006] The purpose of the present invention is to provide a low-nitrogen ultra-high-purity silicon carbide raw material and a synthesis method to solve the problems in the prior art of difficulty in removing internal nitrogen impurities, insufficient process stability, and difficulty in achieving ultra-low nitrogen content.

[0007] The embodiments of this application adopt the following technical solutions:

[0008] A method for preparing low-nitrogen ultra-high-purity silicon carbide raw material comprises the following steps:

[0009] Step 1: Raw material pretreatment

[0010] High-purity silicon powder and high-purity carbon powder were screened and purified separately. The silicon powder particle size was controlled to 1-100μm (D50 = 15μm), with an oxygen content below 0.5ppm. The carbon powder was placed in an argon atmosphere and heated continuously at 2200-2300°C for 8 hours, reducing its initial nitrogen content from 200ppm to below 5ppm. This process eliminates C-N bonds and adsorbed nitrogen through high-temperature graphitization, and X-ray photoelectron spectroscopy (XPS) was used to verify the changes in the chemical bond structure.

[0011] Step 2: Degassing and interface optimization

[0012] Add pre-treated silicon powder and carbon powder into the reaction furnace and evacuate to 2×10 -6 mbar, removing surface adsorbed gases (such as H2O, O2, and N2). Subsequently, an Ar-H2 mixture (with a 5% hydrogen concentration) is introduced at a flow rate of 800 sccm and a pressure of 500 mbar to suppress silicon powder volatilization while forming a uniform Si-C initial contact interface. This step avoids local overheating that can lead to compositional segregation.

[0013] Step 3: Low temperature phase formation

[0014] The temperature of the upper and lower heaters in the reactor is adjusted to 1450°C, and the pressure is reduced to 200-300 mbar. Under these conditions, a solid-phase reaction occurs between the silicon powder and the carbon powder, forming α-SiC crystals. During this stage, the temperature gradient and atmosphere are controlled to minimize the diffusion of nitrogen impurities into the crystal lattice.

[0015] Step 4: High temperature phase inversion

[0016] The three zones of the reactor are simultaneously heated to 1950°C and the pressure is further reduced to 100-200 mbar. During this process, α-SiC crystals gradually transform into β-SiC crystals. Simultaneously, the inert gas flow rate is maintained at ≥1000 sccm and the Reynolds number (Re) is >4000 (turbulent state). This step effectively reduces residual nitrogen impurities through the low-pressure environment and turbulent gas flow.

[0017] Step 5: Sublimation-Condensation Growth

[0018] Adjust the bottom heater temperature of the reactor to 2200°C and the top temperature to 800-1000°C, forming a temperature gradient of ≥1200°C / m with the bottom 2200°C, forming a temperature gradient from bottom to top. The pressure is controlled at 30-60mbar, causing the SiC particles in the high-temperature zone to sublime and directionally desublimate in the low-temperature zone, forming particles with a particle size distribution within the range of 0.5-2mm. This step promotes directional growth of particles by optimizing the temperature gradient and pressure conditions, increasing the bulk density to 1.5g / cm 3 above.

[0019] The reactor's heating system preferably includes three independent temperature-control modules: upper, middle, and lower. Each module is separated by insulation to ensure precise temperature control. The upper heater regulates the top low-temperature zone, the middle heater stabilizes the intermediate transition zone, and the lower heater maintains the bottom high-temperature zone. Each heater is equipped with an independent temperature sensor and feedback control system to monitor and regulate temperature fluctuations in real time.

[0020] Preferably, the gas delivery system includes a multi-stage filtration device and a flow control valve to ensure the purity and flow stability of the input gas. The inert gas (such as argon or an argon-hydrogen mixture) enters the reactor evenly through a porous distributor, forming a laminar or turbulent flow, which enhances the contact efficiency between the gas and the material.

[0021] Another technical problem to be solved by the present invention is to provide a method for detecting and optimizing the performance of a low-nitrogen ultra-high-purity silicon carbide raw material, comprising the following steps:

[0022] Step 1: Nitrogen content detection

[0023] The nitrogen content of the final product was analyzed by secondary ion mass spectrometry (SIMS). The test results showed that the nitrogen content was less than 1×10 16 atoms / cm 3 By comparing the test data under different process parameters, the reaction conditions were optimized to further reduce the nitrogen content.

[0024] Step 2: Full element impurity analysis

[0025] Glow discharge mass spectrometry (GDMS) was used to analyze all elemental impurities in the raw materials and final product. The results showed that the total elemental impurity content was less than 1ppm, with key impurity elements (such as B, Al, Ti, and V) all below 0.1ppm. By strictly controlling the purity of raw materials and process conditions, the ultra-high purity of the final product is guaranteed.

[0026] Step 3: Particle size distribution and bulk density test

[0027] The particle size distribution and bulk density of the final product were tested using a laser particle size analyzer and a tap density analyzer. The test results showed that particles with a particle size distribution within the range of 0.5-2 mm accounted for more than 70%, and the bulk density reached 1.5 g / cm 3 By adjusting the temperature gradient and pressure conditions of the fourth step sublimation-desublimation process, the particle morphology and stacking characteristics are further optimized.

[0028] Preferably, dry dispersion technology is used for particle size distribution testing to avoid possible contamination caused by wet dispersion. Bulk density testing is performed using a standard tap density meter with a vibration frequency set to 300 times / minute and a vibration time of 10 minutes.

[0029] Preferably, an online monitoring system is introduced during the performance testing process to record the temperature, pressure, and gas flow data in the reactor in real time. The process parameters are dynamically adjusted through data analysis software to ensure the stability and consistency of the entire preparation process.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] First, by pre-treating the carbon powder with high-temperature graphitization, the CN bonds and adsorbed nitrogen are destroyed, significantly reducing the initial nitrogen content in the raw materials. Combined with the low-pressure, high-flow gas flow design in the subsequent four-step synthesis process, the diffusion of nitrogen impurities into the crystal lattice is further reduced, resulting in a nitrogen content of less than 1×10 16

[0032] atoms / cm 3 .

[0033] Secondly, a three-stage independent temperature control heating system is used to ensure precise control of the temperature field in the reactor. By adjusting the temperature gradient and pressure conditions, an efficient phase transition from α-SiC to β-SiC is achieved, while promoting directional particle growth and increasing the bulk density to 1.5g / cm 3 above.

[0034] Thirdly, the design of the gas delivery system enhances the contact efficiency between the gas and the material. The laminar flow or turbulent flow formed by the porous distributor effectively removes volatile nitrides (such as SiN x ), further reducing the residual nitrogen impurities.

[0035] Fourthly, the introduction of the online monitoring system enables real-time monitoring of the temperature, pressure and gas flow in the reactor, and dynamically adjusts the process parameters through data analysis software to ensure the stability and consistency of the entire preparation process.

[0036] Fifth, the optimization of performance testing methods ensures the quality reliability of the final product. Through the combined application of secondary ion mass spectrometry (SIMS) and glow discharge mass spectrometry (GDMS), nitrogen content and all-element impurity levels are comprehensively evaluated, providing reliable data support for high-end application scenarios.

[0037] Sixth, the particle size distribution and bulk density test results show that the silicon carbide raw material prepared by the present invention has excellent particle morphology and bulk characteristics, meeting the strict requirements of optical-grade silicon carbide crystals and high-purity semi-insulating SiC single crystals on raw material uniformity.

[0038] Seventh, the design of multi-stage filtration device and flow control valve ensures the purity and flow stability of input gas, providing a reliable gas environment guarantee for the entire preparation process. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 It is the silicon carbide raw material produced by the process of the present invention. DETAILED DESCRIPTION

[0040] The present invention provides a low-nitrogen, ultra-high-purity silicon carbide raw material and synthesis method. The following description, without accompanying figures, details the specific embodiments of the present invention. All steps and process parameters involved in this embodiment are optimized based on actual operating conditions to ensure the feasibility and repeatability of the technical solution.

[0041] In the first raw material pretreatment stage, high-purity silicon powder and high-purity carbon powder are screened and purified separately. The particle size of the silicon powder is controlled between 1 and 100 microns, with a D50 value of 15 microns and an oxygen content of less than 0.5 ppm. This particle size distribution ensures uniform contact between the silicon powder and the carbon powder during the subsequent reaction, while avoiding agglomeration caused by excessively fine particles. The carbon powder is placed in an argon-protected environment and heated continuously at a high temperature of 2200 to 2300 degrees Celsius for 8 hours. During this process, the initial nitrogen content in the carbon powder is reduced from 200 ppm to below 5 ppm, mainly through high-temperature graphitization to destroy C-N bonds and adsorbed nitrogen. After this step is completed, X-ray photoelectron spectroscopy is used to verify the changes in the chemical bond structure on the carbon powder surface, confirming a significant reduction in C-N bonds. During the above operation, the argon flow rate in the high-temperature furnace is controlled at 1000 sccm to ensure the stability of the inert gas environment and effectively remove volatile impurities.

[0042] In the second step of degassing and interface optimization, the pre-treated silicon powder and carbon powder were added into the reactor and vacuumed to 2×10 -6mbar to remove surface adsorbed gases such as H2O, O2 and N2. Subsequently, an Ar-H2 mixed gas is introduced with a hydrogen concentration of 5%, a flow rate controlled at 800sccm, and a pressure maintained at 500mbar. In this step, the presence of hydrogen helps to suppress the volatilization of silicon powder and promotes the formation of a uniform Si-C initial contact interface between silicon powder and carbon powder. The reactor is designed with three independent temperature control modules, namely the upper, middle and lower heaters. The heater power distribution is: 15kW for the upper section, 20kW for the middle section, and 25kW for the lower section. The modules are separated by thermal insulation materials to ensure precise control of the temperature field. Each heater is equipped with an independent temperature sensor and feedback control system to monitor and adjust temperature fluctuations in real time. The gas delivery system includes a multi-stage filtration device and a flow control valve. The input gas enters the reactor evenly through a porous distributor to form laminar flow or turbulent flow, thereby enhancing the contact efficiency between the gas and the material.

[0043] During the third low-temperature phase formation stage, the temperatures of the upper and lower heaters in the reactor are adjusted to 1450°C, and the pressure is reduced to 200 to 300 mbar. Under these conditions, silicon powder and carbon powder undergo a solid-phase reaction to form α-SiC crystals. The key to this stage lies in controlling the temperature gradient and atmosphere conditions to reduce the diffusion of nitrogen impurities into the crystal lattice. The temperature gradient is set by the upper and lower heaters: the upper heater is set to 1480±10°C, and the lower heater is set to 1420±10°C, with a gradient difference of 60°C and a temperature gradient change rate of ≤5°C / min. This avoids phase change stress cracks and forms a top-down heat conduction path. The pressure within the reactor is coordinated by a vacuum pump and a gas flow controller to ensure that the pressure remains stable within the target range. In this step, the porous distributor design of the gas delivery system further optimizes the gas flow path, ensuring uniform gas distribution within the reactor, thereby improving reaction efficiency.

[0044] The fourth step is the high-temperature phase transformation stage, where the three zones of the reactor are heated simultaneously to 1950 degrees Celsius and the pressure is further reduced to 100 to 200 mbar. During this process, α-SiC crystals are gradually transformed into β-SiC crystals, while volatile nitrides such as SiN x Carried away by a large flow of inert gas. In this step, the design of low-pressure environment and turbulent gas flow effectively reduces the residual nitrogen impurities. The middle heater of the three-stage independent temperature control heating system is used to stabilize the temperature of the intermediate transition zone to ensure efficient phase transition from α-SiC to β-SiC. The bottom heater of the reactor is responsible for maintaining the temperature of the high-temperature zone, while the top heater regulates the temperature of the low-temperature zone to form a temperature gradient from bottom to top. The flow regulating valve of the gas delivery system dynamically adjusts the gas flow according to real-time monitoring data to ensure that the gas flow rate and pressure in the reactor are always maintained at the optimal state.

[0045] In the fifth step, the sublimation-desublimation growth stage, the temperature of the bottom heater of the reactor is adjusted to 2200 degrees Celsius, and the top temperature is controlled to 800-1000 degrees Celsius, forming a temperature gradient of ≥1200 degrees Celsius / m with the bottom 2200 degrees Celsius, forming a temperature gradient from bottom to top. The pressure is controlled at 30 to 60 mbar, so that the SiC particles in the high temperature zone sublime and directionally desublimate in the low temperature zone, forming particles with a particle size distribution ranging from 0.5 to 2 mm. In this step, the optimization of temperature gradient and pressure conditions promotes the directional growth of particles and increases the bulk density to 1.5 g / cm 3 The temperature of the reactor's bottom heater is precisely regulated by an independent feedback control system, while the top heater maintains a low temperature via a cooling water circulation system. The gas delivery system's porous distributor design further optimizes the gas flow path, ensuring uniform gas distribution within the reactor, thereby improving the efficiency of the sublimation and desublimation processes.

[0046] In the performance testing and optimization method, the first step is to analyze the nitrogen content of the final product using secondary ion mass spectrometry. The test results show that the nitrogen content is less than 1×10 16 atoms / cm 3 . By comparing the test data under different process parameters, the reaction conditions are optimized to further reduce the nitrogen content. The second step is to use glow discharge mass spectrometry to analyze the total element impurities of the raw materials and final products. The results show that the total element impurity content is less than 1ppm, among which key impurity elements such as B, Al, Ti, V, etc. are all less than 0.1ppm. The third step is to use a laser particle size analyzer and a tap density analyzer to test the particle size distribution and bulk density of the final product. The test results show that the particles with a particle size distribution range of 0.5 to 2 mm account for more than 70%, and the bulk density reaches 1.5g / cm 3 Particle size distribution testing utilizes dry dispersion technology to avoid potential contamination from wet dispersion. Bulk density testing is performed using a standard tap density meter, with a vibration frequency set to 300 times / minute for 10 minutes. The introduction of an online monitoring system enables real-time monitoring of temperature, pressure, and gas flow within the reactor. Data analysis software dynamically adjusts process parameters to ensure stability and consistency throughout the entire preparation process.

[0047] In this embodiment, the selection of all process parameters is based on experimental data and theoretical analysis to ensure that the operating conditions of each step can meet the technical requirements. For example, the high-temperature graphitization time of carbon powder in the first step is set to 8 hours, which is based on the experimental discovery that this time can reduce the nitrogen content to the greatest extent without affecting other properties of carbon powder (see Table 1 for experimental data). The flow rate and hydrogen concentration of the Ar-H2 mixed gas in the second step are selected based on the optimal ratio determined by multiple experiments, which can effectively suppress the volatilization of silicon powder and promote the formation of Si-C interface. The design of the gas delivery system fully considers the uniformity and stability of the gas flow path, and the aperture and distribution density of the porous distributor are optimized and calculated to ensure that the gas forms an ideal laminar or turbulent state in the reactor. The design of the three-stage independent temperature control heating system realizes precise control of the temperature field through the combination of thermal insulation material and independent feedback control, thereby avoiding the influence of local overheating or temperature fluctuations on the reaction process.

[0048]

[0049]

[0050] Table 1

[0051] Table 1 Test methods:

[0052] Nitrogen content: Inert fusion-infrared absorption method (ASTM E1019),

[0053] Graphitization degree: XRD calculation (formula:

[0054] g=(0.3440-d 002 ) / (0.3440-0.3354)),

[0055] Specific surface area: BET nitrogen adsorption method (ISO 9277),

[0056] Oxygen growth: Inert gas fusion-infrared detection (ASTM E1409).

[0057] Key Stats:

[0058] Denitrification efficiency critical point

[0059] The nitrogen content dropped to 4.5 ppm after 8 hours (removal rate of 97.8%), and only dropped by 1 ppm after being extended to 12 hours, and the marginal benefit was significantly reduced (>10 hours denitrification energy consumption increased by 50%, and nitrogen removal increased by <0.7 ppm).

[0060] Structural stability inflection point

[0061] The degree of graphitization reaches 96% in 8 hours (close to the ideal graphite crystal 97%), and the grain size L cIncreased to 72nm (the raw material is only 15nm)

[0062] No substantial improvement in structural parameters after >8 hours (10 / 12 hours L c Only increases by 3-4nm, and the degree of graphitization remains unchanged)

[0063] Balance between specific surface area and pollution risk

[0064] Specific surface area after 8 hours: 65m 2 / g: It can ensure the uniformity of subsequent mixing and avoid excessive surface area causing oxygen adsorption (oxygen increment is only +5ppm)

[0065] The specific surface area dropped sharply to <50m in 10 hours. 2 / g, resulting in insufficient silicon-carbon contact area and decreased reaction efficiency (see Table 2 for verification experiments).

[0066]

[0067] Table 2

[0068] The 10-hour carbon powder with too low specific surface area leads to insufficient silicon-carbon contact, a decrease in phase transformation rate and deterioration of particle uniformity (RSD>25%).

[0069] Therefore, the core basis for choosing 8 hours is:

[0070] Maximum denitrification efficiency: 97.8% removal rate (residual nitrogen ≤ 5ppm), beyond this time only < 0.7ppm nitrogen can be removed;

[0071] Optimized carbon powder structure: 96% graphitization and 72nm grain size, ensuring high reactivity and avoiding over-densification;

[0072] Optimal balance of pollution control: specific surface area 65m 2 / g Control the oxygen increment within 5ppm (<8h will cause more impurities to be adsorbed, >8h will require higher temperature, resulting in a sharp increase in energy consumption);

[0073] Product performance verification: The SiC nitrogen content (0.8×10 16 atoms / cm 3 ) is reduced by 75% compared with 6h, and the phase change rate is increased by 25%.

[0074] This implementation also places particular emphasis on dynamic adjustment and real-time monitoring of process parameters. For example, an online monitoring system uses multiple sensors installed within the reactor to record temperature, pressure, and gas flow data in real time and transmits this data to data analysis software for processing. The data analysis software dynamically adjusts process parameters based on a pre-set algorithm model, ensuring stability and consistency throughout the entire production process. This dynamic adjustment mechanism not only improves process controllability but also significantly reduces the impact of human error on product quality.

[0075] All equipment and materials used in this embodiment are commercially available products, and their specifications and performances meet the technical requirements of the present invention. For example, the maximum operating temperature of the high-temperature furnace can reach 2500 degrees Celsius, and the ultimate vacuum degree of the vacuum pump is 1×10 -7 mbar, and the gas flow controller has an accuracy of ±1%. The selection of these devices ensures precise control of process conditions and reliable operation. Furthermore, the purity and particle size distribution of all raw materials are rigorously screened to ensure they meet the technical requirements of this invention. For example, the oxygen content and particle size distribution of high-purity silicon powder are verified by the supplier with test reports before use. High-purity carbon powder undergoes a high-temperature graphitization treatment before use to ensure that its initial nitrogen content meets the requirements.

[0076] All the test methods involved in this embodiment adopt international standards or industry-wide methods to ensure the accuracy and comparability of the test results. For example, the test conditions of the secondary ion mass spectrometry, including parameters such as beam intensity, scanning range and integration time, are all performed in accordance with standard operating procedures. The test conditions of the glow discharge mass spectrometry are optimized according to the sample characteristics to ensure that all key impurity elements can be detected. The operating parameters of the laser particle size analyzer and the tap density analyzer have also been verified many times to ensure that the test results can truly reflect the physical properties of the sample. The standardization and normalization of these test methods provide reliable data support for the evaluation of product quality.

[0077] This implementation also places particular emphasis on optimizing and adjusting process parameters. For example, by comparing experimental data under different temperature gradients and pressure conditions, the optimal process parameters for the fourth, high-temperature phase transformation stage were determined. By adjusting gas flow and pressure, the particle morphology and stacking characteristics for the fifth, sublimation-desublimation growth stage, were further optimized. These optimization measures not only improved product performance but also significantly enhanced production efficiency and cost-effectiveness.

[0078] In order to better enable relevant personnel in this technical field to fully understand and implement the present invention, the specific implementation principle of the present invention is supplemented below with reference to a specific application scenario.

[0079] In the first step of raw material pretreatment, the processing of high-purity silicon powder and high-purity carbon powder requires special attention to the control of particle size distribution and nitrogen content. For example, in actual operation, the high-purity silicon powder is graded and screened through a vibrating screen to ensure that its D50 value is 15 microns, and the carbon powder is graphitized using a high-temperature heat treatment furnace under an inert gas protection environment. During this process, the argon flow rate is set to 1000sccm to remove volatile impurities. The core of the high-temperature graphitization treatment is to destroy the CN bonds inside the carbon powder and the nitrogen adsorbed on the surface. The effect is confirmed by verifying the changes in the chemical bond structure through X-ray photoelectron spectroscopy. After the above steps are completed, the nitrogen content in the carbon powder is reduced from the initial 200ppm to below 5ppm, providing a low-nitrogen foundation for subsequent processes.

[0080] When entering the second step of degassing and interface optimization, the vacuum degree in the reactor must be precisely controlled at 2×10 - 6 mbar to effectively remove the gas molecules adsorbed on the surface of silicon powder and carbon powder. Subsequently, an Ar-H2 mixed gas is introduced, in which the hydrogen concentration is 5%, the flow rate is set to 800sccm, and the pressure is maintained at 500mbar. In this step, the presence of hydrogen not only suppresses the volatilization of silicon powder, but also promotes the uniform contact between silicon powder and carbon powder, forming a stable Si-C initial interface. The design of the three-stage independent temperature control heating system ensures the precise distribution of the temperature field. The upper heater is set to 1480±10℃, and the lower heater is set to 1420±10℃, with a gradient difference of 60℃ and a temperature gradient change rate of ≤5℃ / min, avoiding phase change stress cracks, thereby forming a top-down heat conduction path. The porous distributor design of the gas delivery system further enhances the uniformity of gas distribution, ensures the formation of laminar or turbulent state, and improves the contact efficiency between gas and material.

[0081] In the third step of low-temperature phase generation, the temperatures of the upper and lower heaters of the reactor are adjusted to 1450 degrees Celsius respectively, and the pressure is reduced to 200 to 300 mbar. Under this condition, silicon powder and carbon powder react in the solid phase to form α-SiC crystals. The temperature gradient is set by the upper and lower heaters in coordination. The upper heater is set to 1480±10℃, and the lower heater is set to 1420±10℃. The gradient difference is 60℃, and the temperature gradient change rate is ≤5℃ / min to avoid phase change stress cracks and reduce the diffusion of nitrogen impurities into the lattice. The pressure in the reactor is coordinated by the vacuum pump and the gas flow controller to ensure that the pressure is stable within the target range. In this step, the porous distributor design of the gas delivery system optimizes the gas flow path, so that the gas is evenly distributed in the reactor, thereby improving the reaction efficiency.

[0082] In the fourth step of high temperature phase transformation, the three zones of the reactor are heated simultaneously to 1950 degrees Celsius and the pressure is further reduced to 100 to 200 mbar. During this process, α-SiC crystals are gradually transformed into β-SiC crystals, while volatile nitrides such as SiN x Carried away by a large flow of inert gas. The design of low-pressure environment and turbulent gas flow effectively reduces residual nitrogen impurities. The middle heater of the three-stage independent temperature control heating system is used to stabilize the temperature of the intermediate transition zone to ensure efficient phase transition from α-SiC to β-SiC. The bottom heater of the reactor is responsible for maintaining the temperature of the high-temperature zone, while the top heater regulates the temperature of the low-temperature zone, forming a temperature gradient from bottom to top. The flow regulating valve of the gas delivery system dynamically adjusts the gas flow according to real-time monitoring data to ensure that the gas flow rate and pressure in the reactor are always maintained at the optimal state.

[0083] In the fifth step of the sublimation-desublimation growth phase, the temperature of the bottom heater of the reactor is adjusted to 2200 degrees Celsius, and the top temperature is controlled at 800-1000 degrees Celsius, forming a temperature gradient of ≥1200 degrees Celsius / m with the bottom 2200 degrees Celsius, forming a temperature gradient from bottom to top. The pressure is controlled at 30 to 60 mbar, so that the SiC particles in the high temperature zone sublime and directionally desublimate in the low temperature zone, forming particles with a particle size distribution ranging from 0.5 to 2 mm. In this step, the optimization of temperature gradient and pressure conditions promotes the directional growth of particles and increases the bulk density to 1.5 g / cm 3 The temperature of the reactor's bottom heater is precisely regulated by an independent feedback control system, while the top heater maintains a low temperature via a cooling water circulation system. The gas delivery system's porous distributor design further optimizes the gas flow path, ensuring uniform gas distribution within the reactor, thereby improving the efficiency of the sublimation and desublimation processes.

[0084] In the performance testing and optimization method, the nitrogen content of the final product was first analyzed by secondary ion mass spectrometry. The test results showed that the nitrogen content was less than 1×10 16 atoms / cm 3 . By comparing the test data under different process parameters, the reaction conditions are optimized to further reduce the nitrogen content. Secondly, the raw materials and final products are analyzed for all-element impurities using glow discharge mass spectrometry. The results show that the total element impurity content is less than 1ppm, among which key impurity elements such as B, Al, Ti, V, etc. are all less than 0.1ppm. Finally, the particle size distribution and bulk density of the final product are tested using a laser particle size analyzer and a tap density analyzer. The test results show that the particles with a particle size distribution in the range of 0.5 to 2 mm account for more than 70%, and the bulk density reaches 1.5g / cm 3Particle size distribution testing utilizes dry dispersion technology to avoid potential contamination from wet dispersion. Bulk density testing is performed using a standard tap density meter, with a vibration frequency set to 300 times / minute for 10 minutes. The introduction of an online monitoring system enables real-time monitoring of temperature, pressure, and gas flow within the reactor. Data analysis software dynamically adjusts process parameters to ensure stability and consistency throughout the entire preparation process.

[0085] In the above steps, the selection of all process parameters is based on experimental data and theoretical analysis to ensure that the operating conditions of each step can meet the technical requirements. For example, the high-temperature graphitization time of carbon powder in the first step is set to 8 hours, based on the experimental discovery that this time can minimize the nitrogen content without affecting other properties of carbon powder. The flow rate and hydrogen concentration of the Ar-H2 mixed gas in the second step are the optimal ratios determined through multiple experiments, which can effectively inhibit the volatilization of silicon powder and promote the formation of Si-C interface. The design of the gas delivery system fully considers the uniformity and stability of the gas flow path. The aperture and distribution density of the porous distributor are optimized and calculated to ensure that the gas forms an ideal laminar or turbulent state in the reactor. The design of the three-stage independent temperature control and heating system realizes precise control of the temperature field through the combination of thermal insulation materials and independent feedback control, avoiding the influence of local overheating or temperature fluctuations on the reaction process.

[0086] Furthermore, an online monitoring system uses multiple sensors installed within the reactor to record temperature, pressure, and gas flow data in real time, transmitting this data to data analysis software for processing. The software dynamically adjusts process parameters based on pre-set algorithms to ensure stability and consistency throughout the entire production process. This dynamic adjustment mechanism not only improves process controllability but also significantly reduces the impact of human error on product quality.

[0087] All equipment and materials used in this embodiment are commercially available products, and their specifications and performances meet the technical requirements of the present invention. For example, the maximum operating temperature of the high-temperature furnace can reach 2500 degrees Celsius, and the ultimate vacuum degree of the vacuum pump is 1×10 -7 mbar, and the gas flow controller has an accuracy of ±1%. The selection of these devices ensures precise control of process conditions and reliable operation. Furthermore, the purity and particle size distribution of all raw materials are rigorously screened to ensure they meet the technical requirements of this invention. For example, the oxygen content and particle size distribution of high-purity silicon powder are verified by the supplier with test reports before use. High-purity carbon powder undergoes a high-temperature graphitization treatment before use to ensure that its initial nitrogen content meets the requirements.

[0088] All the test methods involved in this embodiment adopt international standards or industry-wide methods to ensure the accuracy and comparability of the test results. For example, the test conditions of the secondary ion mass spectrometry, including parameters such as beam intensity, scanning range and integration time, are all performed in accordance with standard operating procedures. The test conditions of the glow discharge mass spectrometry are optimized according to the sample characteristics to ensure that all key impurity elements can be detected. The operating parameters of the laser particle size analyzer and the tap density analyzer have also been verified many times to ensure that the test results can truly reflect the physical properties of the sample. The standardization and normalization of these test methods provide reliable data support for the evaluation of product quality.

[0089] In summary, the present invention successfully realizes the preparation of low-nitrogen ultra-high-purity silicon carbide raw materials through innovative raw material purification process and coordinated control technology, meeting the demand for ultra-high-purity silicon carbide materials in high-end application fields.

[0090] Example 1: Nitrogen impurity removal efficiency of the present invention and CN113371712B

[0091]

[0092]

[0093] Key Difference Analysis

[0094] The core role of carbon powder pre-denitrification

[0095] While the patented method doesn't perform deep denitrification on the carbon powder (it relies solely on high-temperature removal during the reaction), the present invention uses graphitization at 2200-2300°C for 8 hours under argon protection, breaking the CN bonds within the carbon powder and releasing nitrogen (XPS verification shows a 95% reduction in the CN peak area), thus reducing nitrogen input at the source. This is the basis for removing "deeply buried nitrogen impurities."

[0096] Optimization of dynamic denitrification mechanism during the reaction process:

[0097] Low-pressure turbulence design: The present invention introduces a large flow of inert gas during the α→β phase transition stage (100-200mbar) to form turbulence to carry away volatile SiN x ;

[0098] In contrast, the patent reacts at normal pressure or slightly negative pressure, where the gas fluidity is insufficient, causing the nitride to be retained and reintegrated into the crystal lattice.

[0099] Directed impurity removal during sublimation and desublimation stages

[0100] The present invention sublimates SiC and then directionally solidifies it under the conditions of 2200℃ / 30-60mbar through a bottom-up temperature gradient. Nitrogen is enriched in the gas phase due to the difference in segregation coefficient and is extracted. The comparative patent does not have this step and cannot eliminate the nitrogen hidden inside the grains.

[0101] The present invention avoids local nitrogen concentration accumulation by adjusting temperature / pressure / gas flow in real time (such as the fourth-step flow valve dynamically responding to pressure fluctuations); in contrast, the patent relies on static parameter control and has poor consistency.

[0102] Example 2:

[0103] To achieve a final product nitrogen content of <1×10 16 atoms / cm 3 Critical experimental data and failure boundary analysis of key parameter combinations based on multivariate orthogonal experimental design:

[0104] Achieve nitrogen content <1×10 16 atoms / cm 3 Critical process parameter combinations

[0105]

[0106] Measured nitrogen content data for typical parameter combinations (SIMS detection):

[0107]

[0108]

[0109] All combinations meet other basic conditions (such as degassing vacuum ≤ 2×10 -6 mbar, H2 concentration 5%).

[0110] Breakthrough 1×10 16 atoms / cm 3 The core parameter coupling relationship:

[0111] The following conditions must be met simultaneously:

[0112] 1. Toner pretreatment: N residual ≤5ppm(t≥7h,T≥2200℃),

[0113] 2. Phase transformation zone dynamics: P react τ<2.5×10 4 mbar·s (τ is the gas residence time)

[0114] 3. Sublimation, condensation and separation control: (temperature gradient / pressure ratio),

[0115] When P = 50 mbar, ΔT ≥ 1250°C is required → the actual value used is 2200-600 = 1600°C (satisfying 32°C / mbar).

[0116] Achieve nitrogen content <1×1016 atoms / cm 3 Must be strictly coupled:

[0117] Deep denitrification carbon powder (N≤5ppm) + low-pressure turbulent phase conversion (100-200mbar) + high-gradient sublimation (ΔT≥1400℃)

[0118] Any parameter deviating from the critical range will cause the nitrogen content to jump to >3×10 16 atoms / cm 3 (such as groups B1-B3).

[0119] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing low-nitrogen ultra-high-purity silicon carbide raw material, characterized in that: The following steps are involved: Step 1: Raw material pretreatment High-purity silicon powder and high-purity carbon powder were screened and purified separately. The silicon powder had a particle size between 1 and 100 microns, a D50 value of 15 microns, and an oxygen content below 0.5 ppm. The carbon powder was placed in an argon atmosphere and heated at 2200 to 2300 degrees Celsius for 8 hours to reduce its initial nitrogen content from 200 ppm to below 5 ppm. Step 2: Degassing and interface optimization Add pre-treated silicon powder and carbon powder into the reaction furnace and evacuate to 2×10 -6 mbar, remove the surface adsorbed gas, and then introduce Ar-H2 mixed gas, in which the hydrogen concentration is 5%, and the flow rate is controlled at 800 sccm, maintaining the pressure at 500 mbar; Step 3: Low temperature phase formation Adjust the temperature of the upper and lower heaters of the reactor to 1450 degrees Celsius and reduce the pressure to 200 to 300 mbar to allow the silicon powder and carbon powder to undergo a solid-phase reaction to form α-SiC crystals. Step 4: High temperature phase inversion The three zones of the reactor are heated simultaneously to 1950 degrees Celsius and the pressure is further reduced to 100 to 200 mbar to gradually transform the α-SiC crystals into β-SiC crystals. Step 5: Sublimation-Condensation Growth Adjust the bottom heater temperature of the reactor to 2200 degrees Celsius, and control the top temperature to 800-1000 degrees Celsius, forming a temperature gradient of ≥1200 degrees Celsius / m with the bottom temperature of 2200 degrees Celsius, forming a temperature gradient from bottom to top, and control the pressure at 30 to 60 mbar, so that the SiC particles in the high-temperature zone sublime and directionally condense in the low-temperature zone.

2. The method for preparing low-nitrogen ultra-high-purity silicon carbide raw material according to claim 1, characterized in that: The heating system of the reactor includes independent temperature control modules in the upper, middle and lower sections. The modules are separated by insulation materials, and each heater is equipped with an independent temperature sensor and feedback control system.

3. The method for preparing low-nitrogen ultra-high-purity silicon carbide raw material according to claim 1, characterized in that: The gas delivery system includes a multi-stage filtration device and a flow regulating valve. The input gas enters the reactor evenly through a porous distributor, forming a laminar flow or turbulent flow.

4. The method for preparing low-nitrogen ultra-high-purity silicon carbide raw material according to claim 1, characterized in that: The particle size distribution of the SiC particles formed in the fifth step is in the range of 0.5 to 2 mm, and the bulk density reaches 1.5 g / cm 3 above.

5. The method for preparing low-nitrogen ultra-high-purity silicon carbide raw material according to claim 1, characterized in that: During the high-temperature graphitization process of carbon powder, the argon flow rate is controlled at 1000 sccm to ensure the stability of the inert gas environment and effectively remove volatile impurities.

6. The method for preparing low-nitrogen ultra-high-purity silicon carbide raw material according to claim 1, characterized in that: In the third step, the temperature gradient is set by the upper heater and the lower heater. The upper heater is set to 1480±10℃, and the lower heater is set to 1420±10℃. The gradient difference is 60℃, and the temperature gradient change rate is ≤5℃ / min to avoid phase change stress cracks.

7. The method for preparing low-nitrogen ultra-high-purity silicon carbide raw material according to claim 1, characterized in that: In the fourth step, the low-pressure environment and turbulent gas flow are designed to reduce residual nitrogen impurities, and volatile nitrogen compounds are carried away by a large flow of inert gas.

8. The method for preparing low-nitrogen ultra-high-purity silicon carbide raw material according to claim 1, characterized in that: In the fifth step, the particle size distribution test uses dry dispersion technology to avoid contamination that may be introduced by wet dispersion.

9. The method for preparing low-nitrogen ultra-high-purity silicon carbide raw material according to claim 1, characterized in that: During the performance testing process, an online monitoring system is introduced to record the temperature, pressure and gas flow data in the reactor in real time, and dynamically adjust the process parameters through data analysis software.

10. The method for preparing low-nitrogen ultra-high-purity silicon carbide raw material according to claim 1, characterized in that: The nitrogen content of the final product is less than 1×10 16 atoms / cm 3 The total element impurity content is less than 1ppm, and the content of key impurity elements B, Al, Ti, and V are all less than 0.1ppm.

Citation Information

Patent Citations

  • A method for reducing nitrogen impurity content in silicon carbide powder

    CN110203933B

  • A method for preparing low-nitrogen-content silicon carbide powder and silicon carbide single crystals

    CN113371712B